Improved Exponential Type Ratio Estimator of Population Variance - Yadav, Subhash Kumar; Kadilar, Cem (Revista Colombiana de Estadística, 2013)
This article considers the problem of estimating the population variance using auxiliary information. An improved version of Singh’s exponential type ratio estimator has been proposed and its properties have been studied under large sample approximation. It is shown that the proposed exponential type ratio estimator is more efficient than that considered by the Singh estimator, conventional ratio estimator and the usual unbiased estimator under some realistic conditions. An empirical study has been carried out to judge the merits of the suggested estimator over others.